Using STD electronic medical record data to drive public health program decisions in New York City. - Paneth-Pollak R; Schillinger JA; Borrelli JM; Handel S; Pathela P; Blank S (American Journal of Public Health, 2010)
Electronic medical records can house patient information gathered over time and at multiple sites, thus they have the potential to increase continuity of care and improve service delivery in a multiclinic system. The New York City Department of Health and Mental Hygiene implemented an electronic medical record system in its 10 sexually transmitted disease clinics during 2004 and 2005. We examine the use of real-time electronic medical record data analyses to evaluate clinical services or program activities and present 3 examples of such analyses that have led to program improvements. Analyses of electronic medical record data have produced changes in clinical practice that in turn have resulted in more effective staff use, increased disease detection, and increased clinic capacity.